2021
DOI: 10.3390/ijms222313040
|View full text |Cite
|
Sign up to set email alerts
|

BaGdF5 Nanophosphors Doped with Different Concentrations of Eu3+ for Application in X-ray Photodynamic Therapy

Abstract: X-ray photodynamic therapy (XPDT) has been recently considered as an efficient alternative to conventional radiotherapy of malignant tissues. Nanocomposites for XPDT typically consist of two components—a nanophosphor which re-emits X-rays into visible light that in turn is absorbed by the second component, a photosensitizer, for further generation of reactive oxygen species. In this study, BaGdF5 nanophosphors doped with different Eu:Gd ratios in the range from 0.01 to 0.50 were synthesized by the microwave ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…However, the work demonstrates conjugation of Tb 3+ :LaF3 nanoparticles with Rose Bengal via electrostatic interaction of negatively charger functional groups of Rose Bengal photosensitizer and positively charged Tb 3+ :LaF3 nanoparticle surface due to Fvacancies on the surface. In its turn, the Eu 3+ :BaGdF5/SiO2 core/shell nanoparticles loaded with methylene blue photosensitizer demonstrated their efficiency in X-ray induced PDT due to the porous nature of SiO2 shell [25].…”
Section: Introductionmentioning
confidence: 98%
“…However, the work demonstrates conjugation of Tb 3+ :LaF3 nanoparticles with Rose Bengal via electrostatic interaction of negatively charger functional groups of Rose Bengal photosensitizer and positively charged Tb 3+ :LaF3 nanoparticle surface due to Fvacancies on the surface. In its turn, the Eu 3+ :BaGdF5/SiO2 core/shell nanoparticles loaded with methylene blue photosensitizer demonstrated their efficiency in X-ray induced PDT due to the porous nature of SiO2 shell [25].…”
Section: Introductionmentioning
confidence: 98%
“…However, the work demonstrates the conjugation of Tb 3+ :LaF 3 nanoparticles with Rose Bengal via the electrostatic interaction of negatively charged functional groups of Rose Bengal photosensitizer and the positively charged Tb 3+ :LaF 3 nanoparticle surface due to Fvacancies on the surface. In turn, the Eu 3+ :BaGdF 5 /SiO 2 core/shell nanoparticles loaded with methylene blue photosensitizer demonstrated their efficiency in X-ray-induced PDT due to the porous nature of the SiO 2 shell [31].…”
Section: Introductionmentioning
confidence: 99%
“…The morphology, particle size, and luminescent properties of BaGdF 5 nanophosphors doped with different rare-earth elements have been previously discussed in refs [13][14][15][16][17][18][19][20]. In particular, D. Yang et al have reported sub-10 nm BaGdF 5 :Yb 3+ /Tm 3+ up-conversion nanoparticles (NPs) synthesized at 300 • C, stabilized by oleic acid and subsequently loaded by doxorubicin to enhance its anti-cancer activity [17].…”
Section: Introductionmentioning
confidence: 99%